Granular fertilizer caking: A research on the performance evaluation of coating agents - Avsar, Cemre; Ulusal, Aysu (European Journal of Chemistry, 2021)
Caking formation in fertilizer products during handling and storage is a frequently encountered problem. Caked fertilizers become together as lumps, lose their free- flowing properties, and create inefficient applications. Several parameters such as relative humidity and temperature of the environment, pressure by pile height, and physicochemical properties of fertilizer product such as moisture content, presence of fines and chemical composition, etc. cause or accelerate caking mechanism. Internal or external anticaking products have been proved to be effective in preventing the caking of fertilizer particles. Liquid or wax anticaking agents are applied externally as coatings on the fertilizer surface. This study focuses on the performance evaluation of commercially available liquid- wax anticaking agents coated on NP 20-20-0 fertilizer, classified as three main groups: petroleum-derived, alkyl amine-fatty acid containing mixtures and bio- based composition. Caking performance of coating products are evaluated via small-bag storage test in 4 sets, according to the results, petroleum derived and alkyl amine- fatty acid containing anticaking products show similar performance, whereas bio-based products’ performance is moderate. This study focuses on a practical approach that will help fertilizer industry about which type of coating product will be effective on the anticaking properties of nitrogenous fertilizers and gives brief results of the effect of commercially available products with various ranges of chemical composition on the caking process.